2019
DOI: 10.1590/fst.34617
|View full text |Cite
|
Sign up to set email alerts
|

Peach palm flour (Bactris gasipae KUNTH): potential application in the food industry

Abstract: Peach palm flours prepared from the landraces microcarpa (MOF), mesocarpa (MEF), and macrocarpa (MAF) were assessed for their functional and morphological characteristics. The flours had moisture contents in accordance with the current legislation, considerable lipid (≥3.95%) and carbohydrate (≥66.68%) contents, and potential as an energy source (≥300 kcal/100 g). MEF and MAF can be considered rich in dietary fibers since their fiber contents were above 6 g/100 g, which contributes to the nutritional enrichmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 14 publications
5
19
0
3
Order By: Relevance
“…The low total acidity values and pH at 6.0 characterize both types of flour as low acidic products; and the a w at 0.39 and 0.41 values suggest microbiological stability (Jay, 2005). In general, the both types of peach palm flour produced in this study showed similar proximate composition with those reported for peach palm flour produced with fruits from unknown varieties (Ferreira and Pena, 2003;Kaefer et al, 2013;Pires et al, 2019), including total energetic value, which can be considered high since the Daily Reference Intake (DRI) for adults is 2,000 kcal (HHS & USDA, 2015).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The low total acidity values and pH at 6.0 characterize both types of flour as low acidic products; and the a w at 0.39 and 0.41 values suggest microbiological stability (Jay, 2005). In general, the both types of peach palm flour produced in this study showed similar proximate composition with those reported for peach palm flour produced with fruits from unknown varieties (Ferreira and Pena, 2003;Kaefer et al, 2013;Pires et al, 2019), including total energetic value, which can be considered high since the Daily Reference Intake (DRI) for adults is 2,000 kcal (HHS & USDA, 2015).…”
Section: Resultssupporting
confidence: 81%
“…The carbohydrate composition of 17 samples of freeze-dried pulps of Colombian peach palm fruits was investigated in details and starch was the major compound (≈72%, being 95% amylopectin and 5% amylose, on average), whereas other compounds were also reported: total sugars (2.1%), reducing sugars (1.4%), crude fibres (2%), and fibres soluble on neutral (3.9%) and acid detergents (1.8%) ( Leterme et al., 2005 ). The contents of fibre in both the types of peach palm flour are expected to be low, since 21 different genotypes of peach palm fruits also harvested in Northern Brazil showed low total fibre contents (0.87–3.40%, dry basis) ( Carvalho et al., 2013 ); as well as peach palm flour exhibited 5.47% of total fibre contents (5.03% insoluble +0.44% soluble) ( Pires et al., 2019 ); and in another study, a breakfast cereal enriched with whole peach palm fruit presented 3.11% (dry basis) of total dietary fibre contents ( Santos et al., 2020 ). Therefore, considering the high contents of starch in pulps of peach palm fruits, the two types of flour can be considered as starchy food products, and such information are useful to further investigations related to the development of new products, incorporation in existing formulations, as well as stability during storage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence clearly indicates how peach-palm has not only a potential for human nutrition from direct consumption of fruits (Restrepo & Estupiñán, 2007), but also due to its advantages for animal nutrition (Arroyo & Murillo, 2000),…”
Section: Introductionmentioning
confidence: 99%
“…Palabras clave: Bactris gasipaes, Colombia, preferencias de los consumidores, mejoramiento genético, recursos genéticos vegetales, razas nativas. transformation for food industry (Aguiar et al, 2019;Da Costa et al, 2019;Ferrari et al, 2020;Martínez-Girón et al, 2017;Pires et al, 2019), and even from the suitability of its stem fibers for improving construction materials (Vargas, 2015). This raises questions on why, apparently, this knowledge has not properly translated into a progressive refinement of genetic improvement programs that deliver relevant social impacts both on farmers and markets.…”
Section: Introductionmentioning
confidence: 99%